The Antic City of Borsh - Çipa, Kriledjan (European Journal of Multidisciplinary Studies, 2018)
The antic center of Borsh is situated in a 310 meters high hill, to the north of nowadays Borsh village, in the Southwestern part of Albania, on the shores of the Ionian Sea. In antiquity this region was part of antic Chaonia. On this site there have been research and excavations up to 1990 - after that year it remained out of the focus of the archeologists. Renewed fieldwork efforts, coupled with the evaluation of the conservation of this site, shows us that this center has been presented only with the fortification and the results of the archeological excavations in the necropolis, without considering urbanistic and the organization of the settlement. The documentation of all the antic structures identified through archaeological survey helped to create a better idea of the organization of this center, by presenting in these paper the houses and other fortification elements that were not presented on previous publications on this center. Fieldwork combined with the unpublished documentation of archeological excavations conducted in the 1980s offer a new perspective that arises out of the study of the urbanistic, architectural, stratigraphic and role of this site in the regional context. Borsh is a hilly city that serves as a very good representation of this category of antic cities in Chaonia's region.
Keywords: Borsh, Chaonia, Epirus, Fortification, Ionian sea, Hellenistic period, Stratigraphy.